Photodegradation and kinetics of edible oil refinery wastewater using titanium dioxide - Eki T. Aisien (Academy of Science of South Africa, 2021)
Edible oil refinery wastewater (EORW) is one source of environmental pollution in Nigeria. The treatment of EORW before discharge into the environment remains a significant challenge in the edible oil refinery industries. This research was aimed at photocatalytic treatment of EORW using a batch photocatalytic reactor with titanium dioxide photocatalyst. We investigated the physicochemical parameters: chemical oxygen demand (COD), biological oxygen demand (BOD5), oil and grease, phenol, chloride (Cl-), total suspended solids, sulfate (SO42-), and phosphate (PO43-) using American Public Health Association methods. The results showed that the reduction efficiency of the treated EORW with TiO2 catalyst ranged between 65.8% (PO43-) and 87.0% (COD), and the improvement in efficiency was 54.1% (pH) and 60.8% dissolved oxygen. However, the results showed no significant difference (p<0.05) in the control treatment without catalyst. The biodegradability of EORW increased from 0.196 to 0.32. It was observed that the optimum values were an initial EORW concentration of 100 mL/L, irradiation time of 90min, catalyst dose of 1.25 g/L, and an agitation speed of 900 rpm. The kinetics of the photodegradation process was well described by the pseudo-first-order equation (R2>0.96) and pseudo-second-order equation (R2>0.98). The intra-particle diffusion model fairly represented the diffusion mechanism with an R2 value of 0.806. The treated EORW met the most acceptable water quality standards for discharged effluent according to the maximum permissible limits of the Nigerian National Environmental Standards and Regulations Enforcement Agency.